Rewarding Effects of Nicotine in Adolescent and Adult Male and Female Rats as Measured Using Intracranial Self-stimulation. Issue 2 (18th November 2018) - Xue, Song; Behnood-Rod, Azin; Wilson, Ryann; Wilks, Isaac; Tan, Sijie; Bruijnzeel, Adriaan W
Abstract: Introduction: Tobacco is highly addictive, and after the development of dependence, it is difficult to quit smoking. Therefore, it is important to understand the factors that play a role in the initiation of smoking. The rewarding effects of nicotine play a role in the initiation of smoking and the goal of the present study was to determine the rewarding effects of nicotine in adolescent and adult male and female rats. Methods: Male and female Wistar rats were prepared with intracranial self-stimulation (ICSS) electrodes between postnatal day (P) 23 and 33. They were then trained on the ICSS procedure and the effect of nicotine (0, 0.03, 0.1, 0.3 mg/kg) on the reward thresholds and response latencies was investigated during adolescence (P40–59) or adulthood (>P75). Results: Nicotine lowered the brain reward thresholds of the adult and adolescent male and female rats. The nicotine-induced decrease in the reward thresholds was the same in the adult male and adult female rats. However, nicotine induced a greater decrease in the reward thresholds of the adolescent female rats than the adolescent male rats. Nicotine decreased the response latencies of all groups and there was no effect of age or sex. Conclusions: Nicotine enhances reward function and psychomotor performance in adolescent and adult male and female rats. Adolescent female rats are more sensitive to the acute rewarding effects of nicotine than adolescent male rats. Therefore, the rewarding effects of nicotine might play a greater role in the initiation of smoking in adolescent females than in adolescent males. Implications: The great majority of people start smoking during adolescence. The present studies suggest that during this period female rats are more sensitive to the acute rewarding effects of low and intermediate doses of nicotine than male rats. The rewarding properties of nicotine play a role in the initiation of smoking and establishing habitual smoking. Therefore, the present findings might explain why adolescent females are at a higher risk for becoming nicotine dependent than adolescent males.